2010
DOI: 10.1021/om100628f
|View full text |Cite
|
Sign up to set email alerts
|

Switched Stereocontrol in Grubbs−Hoveyda Complex Catalyzed ROMP Utilizing Proton-Switched NHC Ligands

Abstract: Grubbs-Hoveyda and Grubbs III type complexes with ferrocenyl-or -NEt 2 -substituted NHC ligands were synthesized according to standard procedures. The electron donation of the NHC ligands in the respective ruthenium complexes can be modulated by oxidation of the ferrocenyl moiety or by protonation of the amino group. The neutral and the respective cationic (oxidized or protonated) ruthenium complexes were tested in the ROMP of norbornene. The change in the electron donation of the NHC ligands upon protonation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 68 publications
2
44
0
Order By: Relevance
“…Many of these monomers have been polymerized with very high cis selectivity and tacticity control using Mo- and W-derived catalysts, but formed predominantly trans polymers when (PCy 3 ) 2 Cl 2 Ru=CHPh was used. 13 Gratifyingly, we found that in almost every case, 2 yielded a polymer with high cis content approaching 90%. In the cases where cis -selectivity with 2 at RT was below that value, conducting ROMP at −20 °C increased %cis by 6–15% (Table 1).…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Many of these monomers have been polymerized with very high cis selectivity and tacticity control using Mo- and W-derived catalysts, but formed predominantly trans polymers when (PCy 3 ) 2 Cl 2 Ru=CHPh was used. 13 Gratifyingly, we found that in almost every case, 2 yielded a polymer with high cis content approaching 90%. In the cases where cis -selectivity with 2 at RT was below that value, conducting ROMP at −20 °C increased %cis by 6–15% (Table 1).…”
mentioning
confidence: 68%
“…This is particularly surprising since the closely analogues (PCy 3 ) 2 Cl 2 Ru=CHPh is known to give poly-5 with only 11% cis double bonds. 13 In contrast to poly-5 and poly-9 prepared by Mo-based catalysts, 10 no long-range order was observed using either of the Ru-based initiators. With 2 , the formation of atactic polymers can be explained by fast carbene epimerization relative to the rate of propagation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The reaction mixture was stirred for 5 min at ambient temperature. (PPh 3 ) 2 Cl 2 Ru(3-phenylindenylid-1-ene) (9) (158 mg, 0.178 mmol) was added and the vial was re-sealed with a Teflon lined cap. The solution was stirred at ambient temperature for 1 h and then concentrated under reduced pressure to afford a brown solid.…”
Section: General Considerationsmentioning
confidence: 99%
“…Plenio also reported efforts toward using ligand oxidation as a means to bias the intrinsic E : Z selectivities displayed by a Ru catalyst containing a ligand bearing pendant ferrocenyl substituents. 9 Although a handful of redox-switchable ligands have been studied, 10,11 their utility in controlling catalytic reactions is still rather limited. [5][6][7]12,13 This deficiency may be, at least partially, due to the fact that many of the aforementioned ligands are bi-or multi-dentate, which confines their range of possible geometries and catalytically active transition metal complexes into which they may be incorporated.…”
Section: Introductionmentioning
confidence: 99%